Vanadium (V) reduction reaction on modified glassy carbon electrodes – Role of oxygen functionalities and microstructure. (November 2016) - Taylor, Susan M.; Pătru, Alexandra; Streich, Daniel; El Kazzi, Mario; Fabbri, Emiliana; Schmidt, Thomas J.
Abstract: This paper provides valuable insights into the kinetics of the vanadium (V) reduction reaction occurring at a glassy carbon (GC) model electrode surface treated by different oxidative and mechanical methods. Oxidative treatments were applied by thermal, acid and electrochemical means. Mechanical polishing on an abrasive sandpaper surface was used to prepare a rough GC electrode, this surface was also further electrochemically oxidised. The resulting surfaces were studied by x-ray photoelectron spectroscopy (XPS), Raman spectroscopy, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Activity is defined in terms of peak potential separation (ΔEp ) and this descriptor was verified by EIS. No correlation between activity and oxygen to carbon ratio (O/C) or any specific oxygen functional group was found in this study. Raman spectroscopy revealed significant structural changes for GC electrodes treated by electrochemical oxidation and abrasive polishing. A correlation between structural disorder in GC and improvements in activity was observed. However, a limit of structural disorder exists, beyond which no substantial improvements in activity can be achieved. Graphical abstract: